2007
DOI: 10.1007/s00266-006-0191-8
|View full text |Cite
|
Sign up to set email alerts
|

A New Simple Technique for Making Facial Dimples

Abstract: In Asia, especially in China, women think a dimple is an important part of a beautiful smiling face. The dimple can make them more confident. Unfortunately, not all women have dimples. Hence, with the development of the Chinese economy, there is an increasing demand among Chinese women for the creation of dimples. Most women hope the impairment of the operation will be slight and the period of recovery short so they can go to work as quickly as possible. Some of them want to have dimples only when they smile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…Not only women desired cheek dimple but also some men became interested to have dimples. In patients requesting only 1 dimple, the left side was more requested than the right and this finding was also reported by Bao et al 7 The first report for a cheek dimple was published by Boo-Chai. 3 Sporadic reports for creation of cheek dimple then followed.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Not only women desired cheek dimple but also some men became interested to have dimples. In patients requesting only 1 dimple, the left side was more requested than the right and this finding was also reported by Bao et al 7 The first report for a cheek dimple was published by Boo-Chai. 3 Sporadic reports for creation of cheek dimple then followed.…”
Section: Discussionsupporting
confidence: 70%
“…However, the main disadvantage of this technique is the less satisfactory results in 14% of dimples in the form of fading or complete disappearance, which is relatively higher than other previous described techniques. 5,7 CONCLUSIONS All techniques used for creation of dimples have similar principle of making skin adherent to the underlying buccinator muscle. This technique is very simple, rapid, easy to execute, and gives satisfactory results in up to 86% of patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Note that normal human external tissues stretch upto ~20% without tissue damage (Yeo et al 2013b) and typical skin deformation does not exceed the selected bending curvature (Hattori et al 2014a). Overall, the FEA and experimental results ensure that the fractal structure makes a suitable electrode even if a user has unusually developed dimples and habits to create exaggerated facial expressions (Bao et al 2007). …”
Section: Resultsmentioning
confidence: 89%
“…Since Boo-Chai's report of a technique for creating facial dimples in 1962, several authors have described various techniques of creating perioral dimples. Bao et al [5] reported a simple technique in which a syringe needle is used to connect the buccinator muscle to the dermis with non-absorbable suture materials. For long-term results, many surgeons prefer using non-absorbable suture materials, such as nylon or prolene.…”
Section: Discussionmentioning
confidence: 99%